Beneficial use of Ni-rich petroleum coke ashes: Product characterization and effects on soil properties and plant growth - Rodak, Bruna Wurr; Freitas, Douglas Siqueira; de Oliveira Lima, Geraldo Jânio Eugênio; Reis, André Rodrigues dos; Schulze, Joachim; Guilherme, Luiz Roberto Guimarães (Journal of cleaner production, 2018)
Fly and bottom ashes - by-products of petroleum coke combustion - contain important plant nutrients (e.g., Ca, S) and may be used as soil acidity amendments, yet their metals content might be a concern. Finding innovative alternatives for the beneficial use of such by-products is key for assuring their environmental sustainability. In this study, we first carried out a comprehensive characterization of fly and bottom ashes, i.e., physical, chemical, mineralogical, and structural analyzes. Next, we created a new product based on these ashes to meet the demand of the Brazilian legislation. To test the agronomic efficiency of the product and the environmental implications of its agricultural use, greenhouse experiments were performed with two Oxisols, cultivated with maize and soybean. The treatments consisted on the application of two doses of different products, aiming to increase soil base saturation to 50% and 70%, and three sources: 1) a blend of fly and bottom ashes with commercial limestone (blended limestone, BL); 2) a positive control, commercial limestone enriched with Ni and S (enriched limestone, EL); and, 3) a negative control (commercial limestone, CL). The BL was efficient for soil acidity correction, providing Ca, Mg, S, and Ni to maize and soybean plants. Plant dry weight did not change following the application of the product, yet the BL was effective as a Ni-fertilizer, since it was able to increase soil-Ni up to 5-fold, as well as Ni content in maize and in soybean leaves by 5- and 4-fold, respectively, positively affecting N metabolism. Our findings revealed that, while improving many soil attributes, the BL is a viable and sustainable technology for the use of petroleum coke combustion ashes in agriculture, working as a Ni-fertilizer to plants, which meets a current market demand for this micronutrient.